2009
DOI: 10.1091/mbc.e08-04-0438
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Toxicity to Saccharomyces cerevisiae Is a Consequence of Inhibition of the TORC1 Kinase Combined with a Chronic Stress Response

Abstract: The conserved Target Of Rapamycin (TOR) growth control signaling pathway is a major regulator of genes required for protein synthesis. The ubiquitous toxic metalloid arsenic, as well as mercury and nickel, are shown here to efficiently inhibit the rapamycin-sensitive TORC1 (TOR complex 1) protein kinase. This rapid inhibition of the TORC1 kinase is demonstrated in vivo by the dephosphorylation and inactivation of its downstream effector, the yeast S6 kinase homolog Sch9. Arsenic, mercury, and nickel cause redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 65 publications
4
39
0
Order By: Relevance
“…Earlier studies have shown that, in yeast and mammalian cells, complex negative and positive feedback loops exist between Sch9 (or the mammalian Sch9 homolog, S6K1) and the TORC1 network [43, 84, 85]. In addition, some other compensatory pathways may be turned on when Sch9 or TORC1 is compromised [78, 86]. In ancestral tetraploids, Sch9 is downregulated compared to normal diploids.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that, in yeast and mammalian cells, complex negative and positive feedback loops exist between Sch9 (or the mammalian Sch9 homolog, S6K1) and the TORC1 network [43, 84, 85]. In addition, some other compensatory pathways may be turned on when Sch9 or TORC1 is compromised [78, 86]. In ancestral tetraploids, Sch9 is downregulated compared to normal diploids.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, this could be achieved by either a reduction in new ribosome production or an increase in post-translational degradation of ribosomes. A key observation in this regard is that microarray-based studies of the transcriptional response to arsenic have also noted broad reductions in the levels of mRNAs for ribosome components (7,20). These studies did not examine ribosome protein levels or propose that ribosome reduction might be an adaptive cellular response.…”
Section: Proteotoxicity Is a Major Component Of Toxicity For Trivalentmentioning
confidence: 99%
“…Genome-wide analyses of transcription patterns in S. cerevisiae in response to treatment with arsenic have revealed a complex response that influences signaling pathways including protein kinases such as the mitogen-actived protein kinase and target of rapamycin (TOR) complex 1 (TORC1) systems. 39,40 Arsenic toxicity results from inhibition of TORC1 kinase and modulation of the activity of downstream factors, leading to activation of the transcription factors that are targets of TORC1 and protein kinase A. 40 Whether arsenic has similar effects in Candida and Aspergillus spp.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…39,40 Arsenic toxicity results from inhibition of TORC1 kinase and modulation of the activity of downstream factors, leading to activation of the transcription factors that are targets of TORC1 and protein kinase A. 40 Whether arsenic has similar effects in Candida and Aspergillus spp. is unknown.…”
Section: Corticosteroidsmentioning
confidence: 99%